Progression of endolymphatic hydrops and vertigo during treatment in Meniere's disease. (2nd December 2022) - Niu, Yue; Chen, Wei; Lin, Mengyan; Sha, Yan
Abstract: Background: Patients with Meniere's disease (MD) receive treatment to reduce vertigo. Purpose: To explore the fluctuation of vertigo symptoms and the changes in endolymphatic hydrops (EHs) in MD patients during long-term regular medication. Materials and methods: We enrolled MD patients who had received two magnetic resonance imaging with intravenous contrast agents. Results: Of the 42 patients in the study, 18(42.9%) had progressive EHs and 3(7.1%) had remission. The change value of the signal intensity ratio (SIR; cochlear perilymph/cerebellum) on the affected side (1.2) was larger than that on the healthy side (0.9), but there was no statistical difference. Among the 30 patients followed up, two patients had complete control of vertigo, two patients had substantial control, and three patients had worse control. The other 23 patients had insignificant control of vertigo symptoms before and after treatment. The correlation between the progression of cochlear and vestibular hydrops and the improvement of vertigo symptoms in MD patients was not significant. Conclusions and significance: In treated patients with MD, EHs may progress or relieve over the long course of the disease. But there was no correlation between the development of EHs and changes in vertigo symptoms.